Lokalizacja geograficzna jako kontekst badań pedagogicznych. Metodologiczne uwarunkowania komparatystyki edukacyjnej w ujęciu George’a Z.F. Beredaya - Wojniak, Justyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The paper analyses the figure and the achievements of George Zygmunt Fijałkowski-Bereday (1920–1983), an educational comparativist of Polish origin, professor at Columbia University in New York. In his scientific work Bereday was concentrated on the issues of methodology of comparative research in education, which resulted in a scientific study titled Comparative Method in Education first published in 1964. One of main areas of Bereday’s interest in this field was the pursuit of identifying a field of science in which comparative research in education would find its solid roots. Analysis of the specifics of the subject of these studies and their socio-cultural context allowed the author to formulate the conclusion that political geography should be such a “parent” discipline for educational comparative studies. The aim of this study is to reconstruct Bereday’s research approach, based on the analysis of documents: archival materials as well as his works concerning the methodological aspects of comparative research in pedagogy that still are little-known in his country of origin, as well as the aims Bereday attributed to the research in this field
Keywords: comparative education; methodology; educational facts; political geography